1993
DOI: 10.1002/ejsp.2420230105
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the influence as a determinant of assimilation versus contrast

Abstract: In the present study, subjects had to generate an evaluative judgment about a target person on the basis of his behaviour that had both positive and negative implications. In a previous phase of the study that was ostensibly unrelated to the judgment task, the relevant trait categories were primed. Subsequently, half of the subjects were reminded of the priming episode. Consistent with earlier research (e.g. Lombardi, Higgins and Bargh, 1987;Newman and Uleman, 1990)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
218
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 249 publications
(232 citation statements)
references
References 25 publications
13
218
0
1
Order By: Relevance
“…This (unexpected) finding might be accounted for by assuming (1) that the participants in the .25-CP condition and the .75-CP condition noticed that the valence of the targets could be predicted on the basis of the valence of the primes and (2) that they attempted to actively overcorrect for the influence of the primes (see J. Glaser & Banaji, 1999;Greenwald & Banaji, 1995;Strack et al, 1993). On the other hand, given that the latter result was not corroborated by the participant analysis of the response latency data or by the analyses of the error data, it is probably wise not to attach too much weight to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This (unexpected) finding might be accounted for by assuming (1) that the participants in the .25-CP condition and the .75-CP condition noticed that the valence of the targets could be predicted on the basis of the valence of the primes and (2) that they attempted to actively overcorrect for the influence of the primes (see J. Glaser & Banaji, 1999;Greenwald & Banaji, 1995;Strack et al, 1993). On the other hand, given that the latter result was not corroborated by the participant analysis of the response latency data or by the analyses of the error data, it is probably wise not to attach too much weight to it.…”
Section: Discussionmentioning
confidence: 99%
“…Klauer et al (1997) hypothesized that this pattern of results may have been due to the fact that the participants attempted to actively (over)correct for the influence of the primes when the SOA was long (see also J. Glaser & Banaji, 1999;Greenwald & Banaji, 1995;Strack, Schwarz, Bless, Kübler, & Wänke, 1993). On the other hand, one could also expect slow-acting, expectancy-based response strategies to produce CP effects at long SOAs (see de Groot, 1984;den Heyer, Briand, & Dannenbring, 1983;Neely, 1977;Neely, Keefe, & Ross, 1989;Perea & Rosa, 2002;Seidenberg, Waters, Sanders, & Langer, 1984;Tweedy, Lapinski, & Schvaneveldt, 1977).…”
mentioning
confidence: 99%
“…When individuals are made aware of the effects of priming stimuli they engage in correction, consciously or nonconsciously (Strack, Schwarz, Bless, Kübler, & Wänke, 1993). In other words, individuals who know the effects a priming task has on their behavior or goals react in order to overcome or counteract the effect.…”
Section: Priming and Awarenessmentioning
confidence: 99%
“…This same pattern of correction for biased information happens for priming attempts. When individuals are made aware that a priming task serves a purpose -influencing a subsequent task or judgment -they engage in conscious correction (Devine, 1989;Strack et al, 1993) or nonconscious correction (Laran, Dalton, & Andrade, 2011). For example, Lepore and Brown (2002) concluded that priming high-prejudice and low-prejudice participants with the blacks category caused judgments of that same category to be respectively more negative and more positive.…”
Section: Priming and Correctionmentioning
confidence: 99%
“…For example, Glaser and Banaji (1999), in a series of six experiments, reported reverse affective priming, that is, slower responses to targets of valence congruent with the prime than to targets of incongruent valence. They attributed this reverse priming to an over-correction for the biasing effect of the primes (e.g., Greenwald & Banaji, 1995;Stapel, Koomen, & Zeelenberg, 1998;Strack, Schwarz, Bless, Kubler, & Wanke, 1993). Based on the observation of reverse priming with prime-target SOA as short as 150 ms, they theorised that the over-correction was an automatic effect, not requiring deliberate intent by the participants.…”
Section: Over-correction Of Valence?mentioning
confidence: 99%